Penerapan Algoritma Backpropagation dalam Memprediksi Kebutuhan Blangko Sertipikat Tanah pada Kantor BPN Kota Pematangsiantar - Astri Veranita Sinaga; Saifullah Saifullah; Jaya Tata Hardinata (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Pematangsiantar City is one of the regions in Indonesia which has a land area of ​​79.97 KM2. the office of the National Land Affairs Agency is a non-ministerial government institution in Indonesia that has the task of carrying out government duties in the land sector in the city of Pematangsiantar and providing land certificates for the community. A system for predicting the need for blank soil certificates using the Artificial Neural Network method is a method that is able to perform a mathematical process to predict the need for blank certificates for soil certificates using the backpropagation algorithm for data processing implemented with matlab. Data were collected through direct observation and grouped based on the annual need for blango factors. The results obtained from the test are the performance and epoch values ​​where each architecture is not the same. The test results are displayed in the form of a graph comparing the target value with the training and testing process.